The genius and the everyday: stories of women who make music (Revista Argentina de Musicología, 2023)
The four articles included in this dossier focus on diverse epochs and spaces. With them, we aim to show the different paths musicology can take in women and gender studies.
Keywords: Graciela Paraskevaídis; Pauline Viardot; Denis Diderot; Women in Percussion